Pengaruh Profesionalisme, Independensi, Etika Profesi, dan Motivasi Kerja terhadap Kinerja Auditor (Studi Kasus pada Kantor Akuntan Publik di Jakarta Selatan) - Priscilla, Grace; Hasymi, Mhd (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
This research aims to determine the influence of professionalism, independence, professional ethics and work motivation on auditor performance. The data used was obtained by distributing questionnaires to auditors who work at Public Accounting Firms in South Jakarta. The number of samples used was 55 respondents using purposive sampling technique. The analytical methods used in this research are validity testing, reliability testing, classical assumption testing, and hypothesis testing. Data processing in this study used the SPSS 25 application. The research results stated that the variables of professionalism, independence, professional ethics and work motivation partially or simultaneously influenced auditor performance. Keywords: professionalism, independence, professional ethics, work motivation, auditor performance